2022
DOI: 10.1136/annrheumdis-2022-eular.4738
|View full text |Cite
|
Sign up to set email alerts
|

Pos0488 identification of Novel Disease Biomarkers in Systemic Sclerosis Through High-Throughput Proteomics

Abstract: BackgroundSystemic sclerosis (SSc) is an autoimmune disease characterized by vasculopathy, tissue fibrosis and activation of the innate and adaptive immune system. Clinical features of the disease consist of skin thickening and internal organ involvement. Due to the heterogeneous nature of the disease, there is an unmet need of biomarkers for diagnosis, disease progression and response to treatment.ObjectivesThe aim of this study was to explore new serum proteomic fingerprints of clinically defined forms of SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Further analysis showed that 39 analytes were associated with more severe skin disease, including the upregulation of some extracellular matrix components (NOV, THBS4) and downregulation of several growth factor receptors (epidermal growth factor receptor, Delta/notch-like epidermal growth factor-related receptor) and adhesion molecules (integrin subunit alpha V) [6]. More recently, Castro et al [44] assessed the levels of serum proteins from a panel of 92 analytes related to organ damage in a cohort of 72 patients with SSc. Sixteen differentially expressed biomarkers successfully classified patients into three clusters.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Further analysis showed that 39 analytes were associated with more severe skin disease, including the upregulation of some extracellular matrix components (NOV, THBS4) and downregulation of several growth factor receptors (epidermal growth factor receptor, Delta/notch-like epidermal growth factor-related receptor) and adhesion molecules (integrin subunit alpha V) [6]. More recently, Castro et al [44] assessed the levels of serum proteins from a panel of 92 analytes related to organ damage in a cohort of 72 patients with SSc. Sixteen differentially expressed biomarkers successfully classified patients into three clusters.…”
Section: Discussionmentioning
confidence: 98%
“…Cluster one was distinguished from clusters two and three based on the more prevalent internal organ involvement, mainly ILD, skin thickening, and esophageal dysmotility, as well as a higher frequency of anti-Scl-70 antibodies. Also, after performing unsupervised hierarchical analysis, nineteen new circulating proteins (BANK1, BID, CALR, ERBB2IP, FGR, FOSB, FOXO1, INPPL1, MAEA, MAGED1, MAP4K5, NBN, NCF2, PRKAB1, RASSF2, RCOR1, SMAD1, STXBP3, VASH1) involved in various molecular pathways were found to be differentially expressed between the clusters [44].…”
Section: Discussionmentioning
confidence: 99%